Pemberian Pemahaman Mengenai Perilaku Hidup Bersih Dan Sehat (PHBS) dan Protokol Kesehatan Dalam Bepergian di Masa Pandemi Kepada Masyarakat - Taofik Rusdiana; Norisca Aliza Putriana; Muhammad Habil Abrar Alhamdra; Shofiyyah Sayyidah (Journal of Community Development, 2021)
Seeing the development of the COVID-19 and the increasing number of new cases, WHO has published several updates, guidelines, and health protocols regarding this pandemic. The government of Indonesia has issued an appeal to the public to follow this health protocol. Various educational posters and videos have been widely published on social media, television stations and other communication media. One of the programs that the government always socializes during this pandemic is the implementation of Perilaku Hidup Bersih dan Sehat (PHBS) or Clean and Healthy Behavior. The purpose of this Virtual Integrative Community Service program is to find out the level of public knowledge about the importance of PHBS and traveling during a pandemic, especially in the AKB era. The methods used in this activity are surveys on community PHBS, surveys regarding travel activities during the pandemic, making PHBS videos and posters, and webinars on the use of herbs as an antistress and immunity enhancer. The partner community in this online KKN PPM activity is the Langensari village community, Solokanjeruk sub-district in particular and the general public who can access social media. The results of the traveling survey showed that out of 441 respondents, around 332 people did not have plans to travel. Of the 332 respondents who chose not to travel, around 229 respondents argued that they did not have a crucial interest, 142 respondents were worried about contracting COVID-19, 50 respondents said they did not have accommodation, and 102 respondents chose to continue traveling / traveling. The results of the PHBS survey are that most respondents have implemented PHBS with the most results being 99.3%, namely the choice of washing hands and using masks. Respondents who answered no to the third question gave answers to the causes of this in the form of lack of access to information (3.4%), laziness (6.9%), and lack of care (4.1%). The group activities of the 25 KKN-PPM Virtual Integrative have been carried out well and can increase community knowledge of PHBS and health protocols when traveling during a pandemic and increase knowledge about the use and manufacture of herbs to increase immunity.